PHYSIOLOGICAL PROFILE OF SPEED, AGILITY AND JUMPING ABILITY OF ELITE U16 BASKETBALL PLAYERS - Panagiotis Androutsopoulos; Ilias Blantas; Konstantinos Papadopoulos; Konstantinos Lapsanis; Giannis Eleftheriadis; Panagiotis Alexopoulos (Universitas Majalengka, 2022)
The purpose of the study was to record the physiological profile of the U16 elite men basketball players of national teams per playing position as well as to compare the differences of those physiological profiles between the playing positions. The study involved 17 young male basketball players (average weight 84 kg, average height 1.97 cm, average age 15.9 years). Players were classified according to their positions in Guards (G: n = 7), Forwards (F: n = 6), and Centers (C: n = 4). In order to determine the physiological profile of the elite players of the study, tests were performed which were divided into 3 characteristics: speed (5m-10m Sprint), agility (T-drill) and jumping ability / anaerobic power (CMJ, DJ, SJ). In the inductive analysis, the possible differences between the different positions of the players were examined through the one-way ANOVA tests. The main findings suggest that the physiological profile of speed, agility and jumping ability of the U16 male players of the Greek National Basketball Team is at a high level. Specifically, the Guards recorded an average of jump height 41.73 cm for the 3 trials (CMJ, SJ, DJ) and times 0.73 ± 0.03 (s), 1.87 ± 0.04 (s) for the 5m. and 10m. sprints and 8.39 ± 0.23 (s) for the T-drill test. Respectively, the Forwards of the research recorded average jump heights of 40.12 cm for the 3 trials (CMJ, SJ, DJ) and times 0.75 ± 0.07 (s), 1.93 ± 0.12 (s) for the 5m, and 10m sprints, and 8.48 ± 0.47 for the T-drill test. Finally, the Centers recorded an average of jump height 42.82 cm for the 3 trials (CMJ, SJ, DJ) and times 0.74 ± 0.05 (s), 1.89 ± 0.04 (s) for the 5m. and 10m. sprints and 8.48 ± 0.31 (s) for the T-drill test. The findings showed that there were no differences between the 3-position players in the 5m / 10m speed tests as well as in the T-drill agility test. On the other hand, in the jump tests, paradoxically, the elite U16 players from the Centers position had the best performance in general in the 3 jump tests and in particular in the CMJ and SJ and the Guards players had the best performance in the DJ. The Forwards position players had the worst performance in all 3 jump tests.